Necrotizing Enterocolitis: A dreadful condition of premature babies - Deepak sharma (Mashhad University of Medical Sciences, 2014)
NEC is inflammatory necrosis of intestine with most common site being terminal ileum and ascending colon in preterm babies (1). The condition is typically seen in premature infants, and the timing of its onset is generally inversely proportional to the gestational age of the baby at birth, i.e. The earlier a baby is born, longer is the time of risk for NEC in premature babies. The incidence of NEC is inversely proportional to the gestational age and birth weight (2). Baby have initial symptoms which include feeding intolerance, increased gastric residuals, abdominal distension and bloody stools (3). The laboratory triad includes metabolic acidosis, hyponatremia and thrombocytopenia. Pneumatosis intestinalis is the pathognomonic radiological finding in the NEC. Modified Bell's staging is used to stage the NEC. Treatment involves Nil per Oral, supportive care, antibiotics, surgery in advanced stages and parenteral nutrition (4,5). Complication of NEC includes mortality, prolonged NICU stay, intestinal strictures, enterocutaneous fistula, intra-abdominal abscess, cholestasis, and short-bowel syndrome (6,7), neurodevelopmental, motor, sensory, and cognitive problems (8,9).